2012
DOI: 10.5539/jas.v4n9p256
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Source of Priming and Post-priming Storage Duration on Seed Germination and Seedling Growth Characteristics in Wheat (Triticum aestivem L.)

Abstract: This study was designed to investigate the effects of seed storing after priming on germination of two wheat cultivars (Cross Alborz and Sardari). The study consisted of five experiments. In experiments 1-4 we tested seed priming with distilled water (hydro priming), potassium nitrate (KNO 3 ), gibberellin (GA 3 ), PEG-6000 (osmopriming) in different concentrations (50, 100 150 and 200 ppm for GA 3 ) and (1%, 2%, 3% and 4% for KNO 3 ) and times (12, 18, 24 and 30 hours). Germination tests were subsequently per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…2 and 4). Our study is in line with another study in which seedling vigor of wheat was improved by the priming with KNO3 (Shafiei Abnavi and Ghobadi, 2012). Similar results were found in corn when the osmopriming of seed was done with 1% KNO3 (Hadinezhad et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2 and 4). Our study is in line with another study in which seedling vigor of wheat was improved by the priming with KNO3 (Shafiei Abnavi and Ghobadi, 2012). Similar results were found in corn when the osmopriming of seed was done with 1% KNO3 (Hadinezhad et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The data shown in figure 1 and 3 depicts that the osmopriming of rice seed with 0.75% KNO3 is better than all other treatments in term of emergence percentage and MET. Our study is in correspondence with another study who revealed that emergence percentage of wheat seed was decreased with the increase in KNO3 concentration (Shafiei Abnavi and Ghobadi, 2012). This indicates that the KNO3 concentration above than a certain level may not be appropriate for cereals.…”
Section: Discussionsupporting
confidence: 89%
“…The increase in plant height might be due to enhancement of cell elongation, cell division and enlargement by chemical priming. These findings are in accordance with the results reported by Jalilian et al (2014) [11] in barley, Abnavi and Ghobadi (2012) [1] in wheat. The present results that KNO 3 priming increased plant height is in conformity with the study done by Sharma and Bose (2006) [19] in wheat and Srivastava and Bose (2012) [20] in rice.…”
Section: Effect Of Chemical Primingsupporting
confidence: 94%
“…Investigations on treated seeds storage, showed different results. The germination test with wheat primed seeds that stored in general showed that 60 days after seed priming was better than other storage duration after seed priming (Shafiei Abnavi and Ghobadi, 2012). Harmful effects of seed treatment while during storage causes activation of DNA-repair due to development in cell cycle.…”
Section: Discussionmentioning
confidence: 99%